2017
DOI: 10.1049/iet-cta.2016.1319
|View full text |Cite
|
Sign up to set email alerts
|

Towards an improved gain scheduling predictive control strategy for a solar thermal power plant

Abstract: This paper improves a recently proposed gain scheduling predictive control strategy on the ACUREX distributed solar collector field at the Plataforma Solar de Almería. Measured disturbances are an integral part of the plant and while simple classical, series and parallel, feedforward approaches have been proposed and used extensively in the literature, the proposed approach incorporates a feedforward systematically into the predictive control strategy by including the effects of the measured disturbances of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…In [37] a nonlinear continuous time generalized predictive control (GPC) is presented and simulation results are shown. In [38], an improvement of a gain scheduling model predictive controller is proposed and tested on a model of the ACUREX solar field.…”
Section: Solar Field Outlet Temperature Regulator: Nonlinear Model Prmentioning
confidence: 99%
“…In [37] a nonlinear continuous time generalized predictive control (GPC) is presented and simulation results are shown. In [38], an improvement of a gain scheduling model predictive controller is proposed and tested on a model of the ACUREX solar field.…”
Section: Solar Field Outlet Temperature Regulator: Nonlinear Model Prmentioning
confidence: 99%
“…Gain scheduling is a widely exercised control design approach for complex non-linear processes either with time-varying or operating level-dependent behaviours [8]. Gain scheduling is particularly favoured by industries over other non-linear control methods due to its generality, simplicity, and ability to manage control design trade-off [9]. Gain scheduled controllers have been used for steam generator water level control [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results showed the superior performance of the proposed controller as compared to a single local dual‐mode MPC. An improvement to [14] was presented in [15] by including the dynamics of the measured disturbances (solar radiation and the field inlet temperature) to the local process models. Simulation results showed that including the accurate prediction model of the disturbances resulted in a reduction of root mean square error of set‐point tracking of ∼12.55%.…”
Section: Introductionmentioning
confidence: 99%